Creatine kinase activity effects on coordination and physical ability tests in elite classical style wrestlers - Starosta, W.; Hübner-Wozniak, E.; Zurek, P. (International scientific and professional conference on wrestling: "Applicable research in wrestling", 2017)
The aim was gaining the knowledge if the creatine kinase activity (CK) in plasma, which is the index of muscle fibres injuries, has some influence on the movement coordination and physical ability tests results. Eight elite wrestlers took part in the study and they performed a set of 7 efficiency tests during 2 days. The CK activities were marked in mornings - before tests. The lack of statistically significant correlations between test results, expressed by both - the absolute values and by points "T" scale, and the CK activity in plasma was stated. However, it seems that the efficiency tests, especially those engaging upper limbs and the trunk muscles, should not be conducted during large training loads employment because the tests results might be dependent on the level of disturbances of the muscle fibres homeostasis elicited by performed earlier physical effort. Gained results point at the lack of statistically significant relationship between the functional state of muscles and the coordination and physical abilities tests results. It may be elicited by too small examined group. It seems that movement coordination tests (especially those engaging upper limbs and trunk muscles) should not be performed during the large training loads employment. Results reached in such a period may be dependent on the degree of muscles fibres homeostasis disturbances caused by performed earlier physical effort.